Uncertainty principle and orthogonal condition for the short-time linear canonical transform. Issue 6 (September 2016) - Huang, Lei; Zhang, Ke; Chai, Yi; Xu, Shuiqing
Abstract The short-time linear canonical transform (STLCT) is a novel time–frequency analysis tool, which maps the time domain signal into the joint time and frequency domain. This short paper investigates its two theoretical problems. The first one relates to the uncertainty principle in one STLCT domain, and the other one is that coefficients of the short-time linear canonical expansion (STLCE) are of incompleteness. To solve these issues, first, we develop the uncertainty principle in one STLCT domain. Second, the orthogonal condition is proposed to guarantee the completeness of the STLCE coefficients.